Use Of Instagram Social Media As Blitar City Government Branding Program (Rt Keren Case Study Program, Bendogerit Village) - Roifatul Lailin, Ulva; Reta Kusumawijayanti, Anita; Dyan Nofa Harumike, Yefi; Lailatus Saadah, Dwi (International Journal of Science, Technology & Management, 2023)
Social media has developed into a very effective tool for communicating and promoting things in various aspects of life, including in government. Instagram has become a very effective communication and promotion tool in various aspects of life, including in the government sector. As is the case in Blitar City, the RT Keren Program which will be launched in 2022 will use social media to communicate and compare government programs. The “RT Keren” program, which means “Neighborhood Space with Diversity, Religious and Nationalist,” aims to stabilize the community's economy after the COVID-19 pandemic by providing physical and non-physical assistance. The aim of this research is to disseminate and disseminate the use of Instagram as a branding tool for the RT Keren government program in Bendogerit Village, Blitar City. Therefore, researchers will explain how Instagram is used as a branding medium for the RT Keren program in Bendogerit Village, Blitar City. This study was conducted using a qualitative approach and a case study. Meanwhile, the theory used is new media theory. Based on observations, Instagram has developed into an effective platform for promotion and communication as well as branding. The results of previous research or previous research on the subject of this research show relevant facts. Based on the results of studies or research results, it shows that Instagram has become an effective tool for promoting RT. Keren, increases community participation, and strengthens the identity of the Bendogerit region. However, there are some issues that need to be addressed, such as implementing more consistent content management and trying to reach a larger audience. Utilizing social media as a branding tool for government programs is a positive step in encouraging community participation and improving the image of local government. The results of the research that has been carried out show that Instagram is an effective/branding tool in promoting the RT.Keren program, increasing community participation, and strengthening the identity of the Bendogerit region. Instagram social media has become a very influential communication and promotional tool in various aspects of life, including in the realm of government. However, there are several challenges that need to be overcome, such as more consistent content management and efforts to expand audience reach. Utilizing social media as a branding tool for government programs is a positive step in encouraging community participation and improving the image of local government.